Increasing Pancasila Education Learning Outcomes on Pancasila Symbols Material Through the Picture and Picture Learning Model for Grade 1 Students of UPTD SDN 192 Barru - Ikhsan, Ikhwanul; Aulia, Nurul Zahra; Wahyuddin, Wahyuddin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This journal reviews the material of Pancasila symbols through the picture and picture learning model for first grade students of UPTD SDN 192 Barru. This study aims to determine the understanding of Pancasila symbols using the picture and picture learning model in the PPKN learning process in first grade of UPTD SDN 192 Barru. This type of research is classroom action research (PTK). The research instrument is student worksheets (LKPD). The source of research data is the results of observations in class, interviews with homeroom teachers, and students. The results of the study showed that increasing numeracy skills using the picture and picture learning model got good and quite satisfactory results. So it is in accordance with what the teacher expected. In the pre-action cycle, only 4 students completed and 13 students did not complete, while in cycle II, 17 students completed. Overall, student learning outcomes on the material of Pancasila symbols increased at each meeting. The implementation process uses the picture and picture learning model which contains the concept of effective learning on the material of Pancasila symbols in PPKN learning. The impact of the material on the symbols of Pancasila provides a deeper understanding and can understand the content of this material in a more enjoyable, inspiring and meaningful way.